Evaluasi Implementasi Program Berbasis Pemangku Kepentingan Di IKN: Pendekatan PLS-SEM Multigrup Di Seluruh Jenis Infrastruktur: Stakeholder-Based Evaluation Of Program Implementation In IKN: A Multigroup PLS-SEM Approach Across Infrastructure Types - Dewi, Rafama; Soemardi, Biemo W.; Waty, Mega (Media Ilmiah Teknik Sipil, 2025)
The implementation of program management in megaprojects often encounters a gap between strategic planning and field execution. This study evaluates stakeholder perceptions regarding the effectiveness of program implementation and project performance in Indonesia’s Nusantara Capital City (IKN). A quantitative survey was conducted with 200 respondents divided into two infrastructure typologies: Horizontal (roads, area development, water resources) and Vertical (high-rise and low-rise buildings). A 6-point Likert scale questionnaire measured six variables: benefit tracking (X1), resource allocation (X2), coordination (X3), risk management (X4), program implementation (M1), and project performance (Y1). The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and multigroup analysis. In Horizontal projects, coordination emerged as the dominant factor (X3→M1 = 0.546; p = 0.000), with program implementation significantly affecting project performance (M1→Y1 = 0.413; p = 0.000). In Vertical projects, risk management was key (X4→M1 = 0.302; X4→Y1 = 0.412; p = 0.000). The strongest indirect effect was found in the coordination-to-performance path through program implementation (0.259; p = 0.000). R² values indicate strong predictive power for program implementation (Horizontal = 0.617; Vertical = 0.660) and project performance (Horizontal = 0.680; Vertical = 0.597). These findings highlight the importance of context-specific program governance strategies.